Circulating gamma-glutamyl transferase and development of specific breast cancer subtypes: findings from the Apolipoprotein Mortality Risk (AMORIS) cohort - Shackshaft, Lydia (Breast Cancer Res, 2017)
BACKGROUND: Different etiological pathways may precede development of specific breast cancer subtypes and impact prevention or treatment strategies. We investigated the association between gamma-glutamyl transferase (GGT) and development of specific breast cancer subtypes based on oestrogen receptor (ER), progesterone receptor (PR) and HER2 status. METHODS: We included 231,283 cancer-free women in a Swedish cohort. Associations between GGT and breast cancer subtypes were investigated with nested case–control and case–case analyses. We used logistic regression models to assess serum GGT in relation to breast cancer subtype, based on individual and combined receptor status. RESULTS: Positive associations were found between serum GGT and development of ER+, ER− and PR+ breast cancers compared to controls (odds ratio (OR) 1.14 (95% confidence interval (CI) 1.08–1.19), 1.11 (1.01–1.23) and 1.18 (1.12–1.24), respectively) and of ER+/PR+ tumours. We found inverse associations between GGT levels and PR− breast cancers compared to PR+ (OR 0.87 (0.80–0.95)), between ER+/PR− tumours compared to ER+/PR+ tumours and between ER−/PR−/HER+ compared to ER+/HER2 or PR+/HER2 tumours (OR 0.55 (95% CI 0.34–0.90). CONCLUSION: The observed associations between pre-diagnostic serum GGT and different breast cancer subtypes may indicate distinct underlying pathways and require further investigations to tease out their clinical implications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13058-017-0816-7) contains supplementary material, which is available to authorized users.